Disenfranchisement in the course of political reorganization. Accommodation and social assistance for asylum seekers in West Berlin and Hamburg, 1973-1982 - Borgmann, Malte (ERDKUNDE, 2019)
The article examines from a comparative perspective how policy regarding the accommodation and social assistance for asylum seekers in Hamburg and West Berlin shifted in the period between the beginnings of decentralisation in mid-1973 and the 1982 Asylum Procedures Act, as well as how the government of the Federal Republic of Germany and its federal state governments influenced this shift. Because the dispersal of asylum seekers between 1974 and 1982 was based only on non-binding decisions of the Conference of Interior Ministers, German federal states could refuse to actually receive their quota. Most asylum seekers were accused of lying about prior political persecution in their homelands. Moreover, municipalities were forced to bear the financial burden of providing social assistance for unemployed asylum seekers. For these reasons, many German federal state governments set themselves the goal of receiving as few asylum seekers as possible by lowering the standard of accommodation and social assistance available for asylum seekers. Drawing on the written records of senates and districts in the Berlin and Hamburg State Archives, the documents of the state parliaments, and press reports, the article examines the historical context behind the local introduction of measures to deter asylum seekers, which are nowadays better known as being part of national policy.